Enhancing Students' Interests in Learning Mathematics at Grade V SDN 07 Tiumang Through The Everyone is a Teacher Here Strategy - Miyato Miyato (The Future of Education Journal, 2023)
The problem underlying this research is that most students lack interest in mathematics lessons because the core of learning mathematics is reasoning so students are encouraged to look for various reference sources both manually and digitally to understand, analyze, relate one concept to another in mathematics subjects and This process is often confusing for students so that it seems boring. Therefore, to increase interest in learning mathematics, PTK was made for 23 students in class V at SDN 07 Tiumang in April 2022 using the learning strategy of Everyone Is A Teacher Here. This strategy is expected to provide opportunities for each student to become a teacher and teach again to other friends. The method used is the test and questionnaire method. The results showed that there was an increase in students' interest in mathematics as seen from the class average score. The value before the intervention was 16.52%. The value in cycle I increased to 59.12 and there was another increase in cycle II to 82.60. Based on these results it was concluded that the Everyone Is A Teacher Here strategy can increase interest in learning mathematics in grade 5 students at SDN 07 Tiumang.